(untitled) (المجلة الدولية للعلوم التربوية والآداب, 2026)
Anxiety is considered as a major emotion factor affecting the performance of EFL learners. In Iraq, students’ interaction with English is limited to the classroom and traditional teaching based on teacher-learner relations is the main teaching style. Thus, many learners face significant difficulties in the production of the language particularly in terms of speaking and writing. The current study investigates the correlation between foreign language anxiety (FLA) and language production (LP) of Iraqi university EFL learners. In Iraq, the instruction of English is mainly in teacher controlled classroom environments, making it difficult for students to learn to speak and write English. Data were gathered from students of the English Department using a Quantitative design approach via an anxiety questionnaire and speaking/writing task. The descriptive statistics and correlation analyses were then performed. From the results, it can be seen that the moderate to high levels of anxiety experienced by most of the learners is evident. There was a strong negative correlation between levels of anxiety and speaking skills, such as being less fluent, accurate and participating. Writing was also impacted, but less so. This result aligns with the previous studies that showed that speaking is more susceptible to anxiety because it is used immediately and the speaker fears to be evaluated. The study recommends that mitigating factors of anxiety can help to enhance total language performance.